The inhibition/promotion effect of C6F12O added to a lithium-ion cell syngas premixed flame. (13th August 2019) - Liu, Ling; Du, Zhiming; Zhang, Tianwei; Guo, Zidong; He, Mingqian; Liu, Zhaoqing
Abstract: The objective of this study is to investigate the impact of different fractions (0–0.05) of C6 F12 O addition on laminar flame speed of hydrocarbon syngas by varying the fuel/oxidizer equivalence ratio (0.6–1.2) using Bunsen burner method. The determination of the syngas composition comes from the venting gas of lithium-ion cell during thermal runaway. It is found that C6 F12 O is significantly more effective at stoichiometric and fuel-rich conditions compared to lean flames regardless of fuel species, which implies more suitable for syngas/air flame inhibition than CH4 . The laminar flame speeds of syngas/air increased with lower concentration (<0.01) of C6 F12 O when equivalence ratio less than 0.67, while it decreased with arbitrary concentration of C6 F12 O at the condition of equivalence ratio not less than 0.67 due to the increased heat release rate by exothermic reaction involving C6 F12 O. The laminar flame speed was more sensitive to C6 F12 O addition at stoichiometric and fuel-rich conditions due to the inhibitory effect of substances containing fluorine. Comparison between experimental and numerical results shows a better agreement under fuel-lean conditions with lower C6 F12 O additions using a modified mechanism derived from USC Mesh II. Thermodynamic equilibrium calculations and sensitivity analyses are showed separately that the variation of flame radical concentrations is consistent with laminar flame speeds and the lean flames are more sensitive to the reactions containing fluorine compared to rich for syngas/air flame with C6 F12 O addition. Highlights: Venting gases of Lithium-ion cells (LC) during thermal runaway is flammability. Effectiveness of C6 F12 O in suppressing LC syngas/air flames is studied. Kinetic mechanism of C6 F12 O/LC syngas (or CH4 )/air is verified by Bunsen flames. C6 F12 O is more suitable for inhibiting LC syngas flames compared with CH4 .